Pengaruh Alat Bantu Bidang Miring Terhadap Hasil BelajarSenam Lantai Guling Belakang Pada Siswa di SMP Bintang Timur - Rizal Romli Prastya; Rizki Aminudin; Astri Ayu Irawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
Floor gymnastics is exercise that is done on the floor with a mat that serves to reduce the risk of injury when carrying out movements. One of the basic types of gymnastics taught by class VIII semester is practicing the basic back roll or back roll technique. Back bolster is rolling or rolling the body backwards where the position of the body must remain rounded, namely with the legs folded, the knees still attached to the chest then the head is lowered until it is attached to the chest. The use of inclined plane learning media is a way of developing subject matter in an easier and interesting way to be applied in the form of modified learning media so that teaching and learning activities in schools can be conveyed properly. By using this learning media, it is expected to be able to improve students' abilities in learning back roll floor gymnastics. Based on the results of data management using the SPSS version 25 application on descriptive statistics. Before conducting the research, the researcher knew the initial conditions. In the initial test (Pretest) the highest score obtained was 78.00 and the lowest score was 33.00, and the average value was 54.35. Meanwhile, after the treatment, the final test score (posttest) increased back roll ability with the highest score of 100.00 and the lowest score of 56.00 and the average value of 79.37. It can be concluded that the use of inclined plane aids has an influence on the learning outcomes of back roll floor gymnastics in class VIII students at Bintang Timur Junior High School.